Penerapan Asas Ultimum Remedium dalam Pengaturan Kekerasan Seksual:: Analisis Overlapping Crime antara UU TPKS dan KUHP Nasional - Candra, Marli; Abrian, Rizky (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2025)
The principle of ultimum remedium places criminal law as a last resort in resolving social issues, so its application must be selective, proportional, and only used when non-penal efforts are ineffective. In the context of sexual violence, Indonesia has two main legal instruments, namely Law Number 12 of 2022 concerning Sexual Violence Crimes (UU TPKS) and Law Number 1 of 2023 concerning the new Criminal Code (KUHP). Both regulations address sexual violence offenses with overlapping substance (overlapping crime), both in the phrasing of the articles and the penalties. This study aims to analyze the application of the ultimum remedium principle in the regulation of sexual violence, identify forms of overlapping crime, and formulate recommendations for harmonizing criminal law policies in line with the principle of proportionality. The method used is a normative legal approach with an analysis of legislation and relevant literature. The study results indicate that the overlap of norms has the potential to create legal uncertainty and over-criminalization. To address this, the study recommends the harmonization of legal substance and the strengthening of non-penal policies. Recommendations are directed towards the synchronization of the Sexual Violence Crimes Law and the new Criminal Code, as well as the strengthening of strategies to prevent sexual violence through the integration of penal and non-penal policies.